Glutathione S-Transferase Rescues Motor Neuronal Toxicity in Fly Model of Amyotrophic Lateral Sclerosis - Sun Joo Cha; Yeo Jeong Han; Hyun-Jun Choi; Hyung-Jun Kim; Kiyoung Kim (MDPI AG, 2020)
Transactive response DNA-binding protein-43 (TDP-43) is involved in the pathology of familial and sporadic amyotrophic lateral sclerosis (ALS). TDP-43-mediated ALS models in mice, Drosophila melanogaster, and zebrafish exhibit dysfunction of locomotor function, defective neuromuscular junctions, and motor neuron defects. There is currently no effective cure for ALS, and the underlying mechanisms of TDP-43 in ALS remain poorly understood. In this study, a genetic screen was performed to identify modifiers of human TDP-43 (hTDP-43) in a Drosophila model, and glutathione S-transferase omega 2 (GstO2) was found to be involved in hTDP-43 neurotoxicity. GstO2 overexpressed on recovered defective phenotypes resulting from hTDP-43, including defective neuromuscular junction (NMJ) boutons, degenerated motor neuronal axons, and reduced larvae and adult fly locomotive activity, without modulating the levels of hTDP-43 protein expression. GstO2 modulated neurotoxicity by regulating reactive oxygen species (ROS) produced by hTDP-43 in the Drosophila model of ALS. Our results demonstrated that GstO2 was a key regulator in hTDP-43-related ALS pathogenesis and indicated its potential as a therapeutic target for ALS.